Development of emotional state model using electromagnetic signal information for rehabilitation robot - Ghazali, Aimi Shazwani; Sidek, Shahrul Na'im; Fatai, Sado (Taylor and Francis / Atlantis Press, 2016)
The paper presents a development of emotion recognition system which can detect human emotion in real-time leveraging information captured from human body’s electromagnetic (EM) signals. A new model of controller framework was designed to embed the emotion recognition module which was evaluated on a robot-assisted rehabilitation platform. The framework is based on hybrid automata model and used to govern the suitable trajectory to deploy by the robotic platform in assisting rehabilitation therapy. The result of the new controller design demonstrates the efficacy of the approach where emotion of the subject is taken into consideration in switching the rehabilitation tasks.